Developmental reading 1 - Anonat, Rosa Dematera (Mandaluyong City, Philippines : Books Atbp. Publishing Corp., 2016)
This book is for instructional use of any teacher involved in developing theses paramount reading skills. The book covers topics on academic reading, comprehension, structure and concepts in reading, reading varied materials as well as factors contributory to reading achievement.
Quarter 1. Academic reading -- Quarter 2. Efferent and aesthetic reading -- Quarter 3. Reading as a Neuro-Physiological process -- Quarter 4. Intrinsic factors for reading achievement.
Includes bibliographical references.
Keywords: DEVELOPMENTAL READING